Loving nature, praising the creator; The visualizations of the natural world in the Islamic magazine Pandji Masjarakat - Zara, Muhammad Yuanda (UI Scholars Hub, 2022)
This study examines previously unexplored visual representations of the natural world published in Pandji Masjarakat magazine in 1960. Known at the time as the most popular Islamic magazine in Indonesia, this publication not only discussed Islamic teachings as hitherto understood, but also provided ample space for the publication of drawings, paintings, and photographs of the natural world. This study argues that the visualizations of the natural world in Pandji Masjarakat were aimed at providing its Muslim readers all over Indonesia and in the wider Malay world with guidance on how to see the natural world and people’s place in it in proper perspective, namely beautiful nature is Allah’s creation and people are welcome to use it taking full responsibility and expressing proper gratitude for it. This study sheds light on the changing attitude of Muslims to the portrayal of living things by presenting how progressive Muslims represented the natural world visually amid the throes of the rapid physical development in increasingly modernized Indonesia.